Student Wellbeing In Indonesian Context - Merida, Sarita Candra; Febrieta, Ditta (International Journal of Education, Information Technology, and Others, 2023)
5 Juni 2022 10 Juni 2022 13 Juni 2022 Well-being is one of the constructs in positive psychology which is developing. There are happiness, psychological well-being, subjective well-being. For student’s context there are student well-being and school well being. Most student well being measurement in Indonesia use student wellbeing and school well being, but in college students rarely use this concept. Measurement of well-being in college students usually using wellbeing measurement, psychological well-being, and subjective well-being. The purpose of this research to provide an overview of the definitions, dimensions and measurements of student wellbeing in Indonesia. The method used is a literature review using an integrative approach. This integrative technique uses the SALSA (Search, Appraisal, Synthesis, Analysis) from e-resource. For example, Google Schoolar, Dimensions, Elicit.org, E-book and other electronic resources. The results of this research are measurement wellbeing with student wellbeing concept is appropriate for describing the well-being of both students and college students. The dimensions for measuring student wellbeing in Indonesia are physiological, psychological, cognitive, emotional, social, personal, Intrapersonal and spiritual dimensions.